Relationship between oral parafunctional/nutritive sucking habits and temporomandibular joint dysfunction in primary dentition - P. M. CASTELO, M. B. D. GAVIÃO, L. J. PEREIRA & L. R. BONJARDIM (Paediatric Dentistry, 2005)
The aim of this study was to evaluate the relationship between nutritive and parafunctional habits and the presence of temporomandibular dysfunction (TMD) in children with primary dentition.